Absorption of 1.5% glycine after percutaneous ultrasonic lithotripsy for renal stone disease. Issue 6497 (14th September 1985) - Sinclair, J F; Hutchison, A; Baraza, R; Telfer, A B
Abstract : An elderly normotensive man underwent percutaneous ultrasonic lithotripsy for renal stone disease, the procedure lasting three hours and the fragments being washed out with 20 l 1.5% glycine. After two hours the inflation pressure had risen to 25 cm H2O and his blood pressure to 150 mm Hg. Inflation pressure continued to rise until drainage tubes were inserted into the retroperitoneal space, releasing a large volume of fluid, some of which appeared to be from the peritoneal cavity. Shortly after transfer to the recovery area the patient showed signs of the transurethral resection syndrome, with hyponatraemia, hyperkalaemia, and hypertension. He was treated appropriately and survived. Low infusion pressures should be used for irrigation during lithotripsy and 0.9% saline instead of 1.5% glycine. In patients given a general anaesthetic any rise in inflation pressure suggests extravasation of fluid and warrants emergency estimation of the plasma sodium concentration.